Synthesis of novel quinoline–based 4,5–dihydro–1H–pyrazoles as potential anticancer, antifungal, antibacterial and antiprotozoal agents - Ramirez Prada, Jonathan (2017)
A new series of N–substituted 2–pyrazolines 9a–f, 10a–f, 11a–f, 12a–f and 13a–f were obtained from the cyclocondensation reaction of [(7–chloroquinolin–4–yl)amino]chalcones 8a–f with hydrazine hydrate and its derivatives. Fourteen of the synthesized compounds including the starting chalcones were selected by US National Cancer Institute (NCI) for testing their anticancer activity against 60 different human cancer cell lines, with the most important GI50 values ranging from 0.28 to 11.7 μM (0.13–6.05 μg/mL) and LC50 values ranging from 2.6 to > 100 μM (1.2 to > 51.7 μg/mL), for chalcones 8a,d and pyrazolines 10c,d. All compounds were assessed for antibacterial activity against wild type and multidrug resistant gram negative and gram positive bacteria, with MIC values ranging from 31.25 to 500 μg/mL. Additionally, the novel compounds were tested for antifungal and antiparasitic properties. Although these compounds showed mild activity against Candida albicans, chalcones 8a and 8e showed high activity against Cryptococcus neoformans with MIC50 = 7.8 μg/mL. For anti–Plasmodium falciparum activity the 2–pyrazoline 11b was the most active with EC50 = 5.54 μg/mL. Regarding the activity against Trypanosoma cruzi, compound 10a was highly active with EC50 = 0.70 μg/mL. Chalcone 8a had good activity against Leishmania panamensis amastigotes with EC50 = 0.79 μg/mL.